Home advantage in combat sports during the Olympic Games - Franchini, E.; Takito, M. Y. (Sport Sciences for Health, 2016)
Purpose: To determine if there is a home advantage effect in combat sports (boxing, fencing, judo, taekwondo and wrestling) in the Olympic Games during the period between 1996 and 2012. Methods: This study analyzed the performance of United States of America, Australia, Greece, China and Great-Britain in this period, considering only boxing, fencing, judo, taekwondo and wrestling. Relative frequency was calculated considering number of medals won by each country as a percentage of the total number of medals disputed in these sports. A multilevel mixed-effects Poisson regression was used to estimate the incidence rate ratio (IRR) and 95 % confidence intervals (95 % CI) for the association of factor of interest as hosting country and country. In multilevel analyses, total number of medals disputed in each sport was included as the exposure in the models. As athletes in each sport changed over time, they were included as random parameters. All significance tests were 2-tailed, and p values less than 0.05 were considered statistically significant. Results: There was a home advantage effect for total number of medals [IRR[95 % CI] = 1.97 (1.38-2.80); p < 0.001], gold [IRR[95 % CI] = 2.62 (1.45-4.73), p = 0.001] and silver medals [IRR[95 % CI = 2.13 (1.09-4.17); p = 0.027] adjusted for the total number of medals disputed in each situation, country and sport. However, there was no effect for bronze medals [IRR[95 % CI = 1.40 (0.78-2.51); p = 0.267]. Conclusion: This study provided evidence for the home advantage effect in combat sports during the Olympic Games disputed between 1996 and 2012 for total number of medals, gold and silver medals, doubling the quantity won when competing at home.